Distribution of plasma concentrations of first-line anti-TB drugs and individual MICs: a prospective cohort study in a low endemic setting. (14th August 2018) - Niward, Katarina; Davies Forsman, Lina; Bruchfeld, Judith; Chryssanthou, Erja; Carlström, Oskar; Alomari, Teba; Carlsson, Björn; Pohanka, Anton; Mansjö, Mikael; Jonsson Nordvall, Michaela; Johansson, Anders G; Eliasson, Erik; et al.
Abstract: Background: Therapeutic drug monitoring (TDM) could improve current TB treatment, but few studies have reported pharmacokinetic data together with MICs. Objectives: To investigate plasma concentrations of rifampicin, isoniazid, pyrazinamide and ethambutol along with MICs. Methods: Drug concentrations of rifampicin, isoniazid, pyrazinamide and ethambutol were analysed pre-dose and 2, 4 and 6 h after drug intake at week 2 in 31 TB patients and MICs in BACTEC 960 MGIT were determined at baseline. The highest plasma concentrations at 2, 4 and 6 h post-dose ( C high ) were determined, as well as estimates of C high /MIC and area under the concentration–time curve (AUC0–6 )/MIC including the corresponding ratios based on calculated free-drug concentrations. This trial was registered at www.clinicaltrials.gov (NCT02042261). Results: After 2 weeks of treatment, the median C high values for rifampicin, isoniazid, pyrazinamide and ethambutol were 10.0, 5.3, 41.1 and 3.3 mg/L respectively. Lower than recommended drug concentrations were detected in 42% of the patients for rifampicin (<8 mg/L), 19% for isoniazid (<3 mg/L), 27% for pyrazinamide (<35 mg/L) and 16% for ethambutol (<2 mg/L). The median C high /MIC values for rifampicin, isoniazid, pyrazinamide and ethambutol were 164, 128, 1.3 and 2.5, respectively, whereas the AUC0–6 /MIC was 636 (range 156–2759) for rifampicin and 351 (range 72–895) for isoniazid. Conclusions: We report low levels of first-line TB drugs in 16%–42% of patients, in particular for rifampicin. There was a wide distribution of the ratios between drug exposures and MICs. The future use of MIC determinations in TDM is dependent on the development of a reference method and clinically validated pharmacokinetic/pharmacodynamic targets.